Issues in HRM policies - Public vs. Private Sector Banks - Kaur, Amrik (Gyan Management Journal, 2017)
Human Resources play an integral role in achieving the individual, organizational, societal and national objectives. Human Resource Management is concerned with the efficient management of human resources by focusing on policies and system of an organization.As far as the present scenario in Indian Banking sector is concerned it is going through a paradigm shift. Indian Banking system mainly comprises Public and Private sector banks whereas the Public Sector Banks which are the backbone of the Indian Banking sector account for more than 78 per cent of the total banking industry assets still found it difficult to compete with their private counterpart. One of the major reasons behind it is the successive failure of their Human Resource Management Policies. Public sector banks still stick to an industry-wide wage settlement, brokered by IBA once every five years. The salary structure of all public sector banks was uniform but ideally, it has not been linked to the profitability of the organization and cost& performance of the employee. The present study is an attempt to examine and compare the issues involved in various human resource management policies of public and private sector banks with respect to some areas of concern such as recruitment, selection and promotion, compensation, training and development policies.
Keywords: Human; individual; organizational; Banking; compensation; promotion